2009
DOI: 10.1007/s00402-009-0972-z
|View full text |Cite
|
Sign up to set email alerts
|

Spondylodiscitis in the elderly patient: clinical mid-term results and quality of life

Abstract: Ultimately, if surgery is indicated the operative risks should be borne in mind, but advanced age should not be the crucial factor in decision-making.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 32 publications
4
55
2
2
Order By: Relevance
“…With the surgical risks in mind, conservative therapy often is the primary option for elderly patients and for patients in poor general condition [27].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…With the surgical risks in mind, conservative therapy often is the primary option for elderly patients and for patients in poor general condition [27].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…For example, due to the risks associated with surgery, conservative therapy is often considered the best option for very elderly or weak patients [8]. On the other hand, because long-term immobilization of the spine is an important part of conservative therapy, clinicians must also weigh the dangers of bed rest (e.g., deep vein thrombosis, muscular atrophy, and pneumonia), especially for elderly patients, against the aforementioned risks of surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,10,13,14 The overall mortality of spondylodiscitis is 5-10%, [2][3][4]7,15 but studies reporting outcome after surgical treatment are scarce, and few studies have reported the health-related quality of life (HRQL) after surgery. [16][17][18][19][20] A few studies have shown that a preoperative neurological deficit is a predictor of a negative outcome, 4,8,9 and neurological deficits are more often present when the spinal infection affects the cervical or thoracic regions. 8 No studies so far have examined HRQL in these groups.…”
Section: Introductionmentioning
confidence: 99%